THE HISTORY OF BUDDHISM IN BANGLADESH: A STUDY OF BUDDHIST SOCIORELIGIOUS AND CULTURAL IDENTITY - Chakma, Jhubhur (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2024)
This study explores the two distinct forms of Buddhism in Bangladesh—Bengali and Jumma Buddhism. Bengali Buddhism, associated with the Barua community and integrated into the dominant Bengali-Muslim identity. On the other hand, Jumma Buddhism refers to the multicultural and linguistic indigenous Buddhist communities in the Chittagong Hill Tracts (CHT). It investigates how the Bangladeshi state imposes Bengali identity and Islamic culture on these diverse multi-ethnic, multi-linguistic indigenous populations by classifying Jumma peoples as “small or sub-tribal” rather than “indigenous or Jumma.” This legal and cultural framing facilitates identity erasure and cultural assimilation. The study employs a documentary research approach and qualitative textual analysis of constitutional documents, scholarly works, and human rights reports to examine how these identities are constructed and marginalized. Findings reveal that although Bengali and Jumma Buddhists appear to coexist, Jumma Buddhists continue to face systematic exclusion, state-led violence, and loss of cultural autonomy. This marginalization contradicts the core Buddhist values of mettā (loving-kindness), karuṇā (compassion), and upekkhā (equanimity). The study calls for formal recognition of Jumma identity and the application of Buddhist ethical frameworks to promote meaningful coexistence, peacebuilding, and the protection of indigenous rights within the national framework of Bangladesh. This study suggests exploring the lived experiences of the Jumma Buddhists and the role of Buddhism in resisting cultural homogenization for further research in this field.